Synthesis and properties of poly(1, 3-dioxolane) in situ quasi-solid-state electrolytes via a rare-earth triflate catalyst. Issue 64 (20th July 2021) - Yang, Guanming; Zhai, Yanfang; Yao, Jianyao; Song, Shufeng; Lin, Liyang; Tang, Weiping; Wen, Zhaoyin; Hu, Ning; Lu, Li
Abstract : Quasi-solid-state polymer electrolytes in situ initiated by abundant rare-earth triflate catalysts will produce intimate electrolyte/electrodes interfaces and enable lithium metal anodes. Abstract : We report a rare-earth triflate catalyst Sc(OTf)3 for the ring-opening polymerization of 1, 3-dioxolane and the in situ production of a quasi-solid-state poly(1, 3-dioxolane) electrolyte, which not only demonstrates a superior ionic conductivity of 1.07 mS cm −1 at room temperature, but achieves dendrite-free lithium deposition and a high Coulombic efficiency of 92.3% over 200 Li plating/striping cycles.